The Influence of E-WoM, Brand Attitude, and Brand Love on Online Consumer Purchase Intentions for Halal Skincare Products - Putri Silvia Istiqomah; Anton Agus Setyawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the influence of Electronic Word of Mouth (E-WoM), brand disposition, and brand affection on consumers’ online purchase intentions specifically within the halal skincare product segment. Grounded in the Theory of Planned Behavior and the Affect Transfer Theory, this research explores how cognitive and emotional brand evaluations, combined with peer-generated online information, shape consumer decision-making in a faith-driven market. While prior studies predominantly emphasized affirmative word of mouth or examined these variables in isolation within conventional cosmetic contexts, this study integrates them in the emerging domain of halal skincare a sector where ethical alignment and perceived credibility are crucial. The research focuses on The Originote, a halal-certified skincare brand, with a purposive sample of 229 respondents including potential buyers, current users, and past consumers of the brand. This sampling method was selected to ensure participants had relevant exposure or intent toward halal skincare, though it limits broader generalization. Data were analyzed using SEM-PLS (version 3.2.9). Findings confirm that E-WoM, brand disposition, and brand affection each have a significant and positive effect on online purchase intention. Furthermore, the study highlights that various forms of E-WoM, such as customer reviews, product ratings, and influencer endorsements, differentially influence purchasing behavior, underscoring the strategic value of digital engagement in halal consumer markets.